Time to treatment and the impact of a physician on prehospital management of acute ST elevation myocardial infarction: insights from the ASSENT-3 PLUS trial. Issue 11 (17th March 2005) - Welsh, R C; Chang, W; Goldstein, P; Adgey, J; Granger, C B; Verheugt, F W A; Wallentin, L; Van de Werf, F; Armstrong, P W
Abstract : Objectives: To assess the impact of variation in prehospital care across distinct health care environments in ASSENT (assessment of the safety and efficacy of a new thrombolytic) -3 PLUS, a large (n  =  1639) contemporary multicentred international trial of prehospital fibrinolysis. Specifically, the objectives were to assess predictors of time to treatment, whether components of time to treatment vary across countries, and the impact of physician presence before hospitalisation on time to treatment, adherence to protocol, and clinical events. Methods: Patient characteristics associated with early treatment (⩽ 2 hours), comparison of international variation in time to treatment, and components of delay were assessed. Trial specific patient data were linked with site specific survey responses. Results: Younger age, slower heart rate, lower systolic blood pressure, and prior percutaneous coronary intervention were associated with early treatment. Country of origin accounted for the largest proportion of variation in time. Intercountry heterogeneity was shown in components of elapsed time to treatment. Physicians in the prehospital setting enrolled 63.8% of patients. The presence of a physician was associated with greater adherence to protocol mandated treatments and procedures but with delay in time to treatment (120 v 108 minutes, p < 0. 001). Conclusion: Country of enrolment accounted for the largest proportion of variation in time to treatment and intercountry heterogeneity modulated components of delay. The effectiveness and safety of prehospital fibrinolysis was not influenced by the presence of a physician. These data, acquired in diverse health care environments, provide new understanding into the components of prehospital treatment delay and the opportunities to further reduce time to fibrinolysis for patients with ST elevation myocardial infarction.